Proteins inhibiting angiotensin converting enzyme derived from pleurotus pulmonarius mycelium (FR.) quél / Badjie Xietaqieuallah Binti Ibadallah - Ibadallah, Badjie Xietaqieuallah (2015)

(untitled)
Pleurotus pulmonarius (grey oyster mushroom) is a well-known edible mushroom that has been acknowledged as a curative agent for many diseases. The antihypertensive potential of Pleurotus pulmonarius mycelium was investigated in vitro via angiotensin converting enzyme (ACE) inhibitory activity. The study was commenced with cultivation of P. pulmonarius mycelium using small scale liquid submerged fermentation for seven days in which brown sugar-spent yeast medium was used as substrate. The mycelial yield was separated from the whole broth to produce mycelial aqueous extract and broth extract, respectively. A preliminary ACE inhibitory assay was performed on the mycelial aqueous extract and broth extract. The result demonstrated almost twofold higher anti-ACE activity of the mycelial aqueous extract at the IC50 value of 0.72 mg/ml. Ammonium sulphate precipitation was therefore carried out on the mycelial aqueous extract for protein extraction and fractionations. Proteins were fractionated into ten fractions based on gradual ammonium sulphate saturation and labelled as F10 to F100. Each fraction was tested for their ACE inhibitory activity and result showed the highest activity by F40 with the IC50 value obtained was 0.022 mg/ml, which was 32 times stronger than the IC50 value of mycelial aqueous extract. Fraction F40 was subjected to RP-HPLC for protein purification using a semi-preparative column C18 (10 × 100 mm). Eight apparent chromatogram peaks were observed and labelled as P1 to P8. All peaks were evaluated for their ACE inhibitory activity and P6 demonstrated the highest ACE inhibitory activity at the IC50 value of 0.012 mg/ml. The IC50 value of P6 was 60 times stronger than that of the mycelial aqueous extract, and considered among the strongest IC50 values for ACE inhibitory activity discovered from mushrooms. Proteins from P6 were further analysed via SDS-PAGE. Consequently, there were four protein bands emerged via silver staining method. Each band was then excised and treated with trypsin in-gel digestion prior to MALDI-TOF/TOF MS. Database search from MALDI-TOF/TOF MS has nominated three potential antihypertensive proteins that work via different mechanisms; serine proteinase inhibitor-like protein, nitrite reductase-like protein and DEAD/DEAH box RNA helicase-like protein. MRPS5-like protein could also be one of the desired proteins due to the highest protein score among all other proteins in MALDI database. Fraction P6 was also subjected to LC-MS/MS to support the protein identification. DEAD/DEAH box RNA helicase-like protein was the only protein that has been identified in both mass spectrometries. This study demonstrated the first reported ACE inhibitory activity from the mycelium of P. pulmonarius (Fr.) Quél cultivated locally.